The Role of Ethical Leadership in Sustainable Performance: An Analytical Research from the Perspective of Al-Muqdadiya Hospital Employees. - Hussein Ali Ibrahim*, Ali; Adnan Hasan , Ali (Journal of Economics and Administrative Sciences, 2024)
Purpose: This research seeks to identify ethical leadership and sustainable performance from a theoretical perspective.Theoretical Framework: Based on what researchers (Kyalo, 2019) reported, these organizations must adopt one of the leadership styles that helps them enhance their reputation from an ethical standpoint in the society within which they operate.Design/Methodology/Approach: The study analyses hospital data (2023-2024), using the ethical leadership model with its three components (justice, power sharing, and role clarification) in enhancing sustainable performance with its three components (social performance, economic performance, and environmental performance).Findings: The results confirmed the existence of a vital role for ethical leadership in enhancing the sustainable performance of Al-Muqdadiya Hospital, and therefore the hypotheses of this research (main and subsidiary) were accepted.Research Implications: The results confirm the need for Al-Muqdadiya Hospital to form a work team of leaders who are distinguished by ethical principles and adhere to them when carrying out the tasks and duties assigned to them, in a way that enhances their role in investing the resources available to the hospital when meeting the standards and indicators of sustainable performance that it seeks.Originality/Value: This study confirms that modern business organizations of all types, as well as the sector in which they operate, need to strengthen their relationship with the environment in which they operate, due to the wide wave of environmental transformations, as well as the rapid changes that the world is witnessing, specifically in the ethical and social aspects.JEL Classification: M10, M12, M15, M19.Authors’ individual contribution: Conceptualization — A.H.A.I..; Methodology — A.H.A.I..; Formal Analysis — A.H.A.I..; Investigation — A.H.A.I.; Data Curation — A.H.A.I..; Writing —Original Draft — A.H.A.I..; Writing — Review & Editing — A.H.A.I.; Visualization — A.H.A.I.; Supervision — A.H.A.I.; Project Administration —A.H.A.I.Declaration of conflicting interests: The Authors declare that there is no conflict of interest.